Retroviruses, retroelements and their restrictions - Atsushi Koito (Frontiers Research Topics, 2015)
Human retroviruses, HIV and HTLV have been recognized as important pathogens because of their association with lethal diseases such as AIDS and ATL. Considerable resources and efforts have been directed at understanding the interaction between these retroviruses and their host which may provide clues as to how the infection can be controlled or prevented. Among the key scientific successes is the identification of intracellular "restriction factors" that have evolved as obstacles to the replication of pathogens including infectious retroviruses. The discovery of APOBEC, which are strong mutagens of retroviral genomes and intracellular retroelements, began a new era of intense research activities into the spectrum of intrinsic anti-HIV activity, leading to the identification of TRIM5a, BST2/Tetherin, and SAMHD1. In response, HIV has evolved several accessory genes as weaponries to evade these intracellular restriction activities. The intracellular antiretroviral defenses evolved in response to endogenous retroelements that make up more than 40% of the entire mammalian genome, and which are regarded as ancestors of infectious retroviruses. LTR-type retroelements are present in all higher eukaryotes, representing about 8% of the human genome. Non-LTR retroelements can be found at extremely high copy numbers also, with a significant portion of mammalin genomes consisting of LINEs. Mammalian genomes are modified by LINEs through insertions, but also by the indirect replication of non-autonomous retrotransposons such as SINEs. LINEs insertion was shown to have played, and continue to play important roles in genomic evolution and somatic genome mosaicism-mediated physiology. And, because retrotransposition can confer genetic diversity that is beneficial to the host, the vertebrate intrinsic immunity has evolved to support a balance between retroelement insertions that confer beneficial and those that cause deleterious gene disruptions. The articles published in this Research Topic should serve not only as valuable references for the field, but provide future topics of research for investigators that should further our understanding of the retrovirus, retroelements and their restrictions.